Architecture of Stalin’s Prison Camps in Yakutia - Kradin, Nikolai (project baikal, 2014)
Based on archive and field studies, the article considers architecture of prison camp facilities built on the territory of Yakutia during Stalin’s terror. With the help of field studies, measurements and photofixation we have revealed compositional, planning and design features of bridges and prison camp facilities and analyzed their location.
Keywords: Yakutia; Ust-Nera; camp barracks; bridges and roads; Hare’s Loop; Black Prizhim; Yellow Prizhim